Resource Aspects in The Successful Implementation of Community Health Centers Accreditation Policy in Makassar City - Irmina Adi Ringrih; Mutmainnah; Ince Annisah Adawiyah Arifin (Institut Teknologi Kesehatan Dan Sains Wiyata Husada Samarinda, 2024)
Accreditation of community health centers is a strategy of the Ministry of Health aims to equalize access and quality of health services, especially in community health centers. The aim of this research is to analyze communication aspects in the implementation of public health center accreditation policies in Makassar. This research uses a descriptive exploratory analysis method with a qualitative approach by means of observation, in-depth interviews and literature studies with all research informants. The variable in the research is communication where communication includes transmission, clarity and consistency. The results of the research show that the resources in the successful implementation of the public health center accreditation policy in Makassar City can be concluded that human resources have met the staffing standards based on Minister of Health Regulation 43 of 2019 for both inpatient and non-inpatient community health centers, however there are several officers who have a workload which is excessive. Facilities and infrastructure at community health centers are adequate and around 60–80% are available, however there are community health centers whose buildings are damaged and need repair, as well as community health center buildings that do not meet the standards of Minister of Health Regulation 43 of 2019. It is hoped that there will be an equal distribution of duties and responsibilities by the leadership to each officer/staff. For infrastructure, it is hoped that more attention will be paid to the completeness of supporting facilities such as the provision of wastewater treatment plants and buildings that comply with regulations.